Pengaruh Pendidikan Kesehatan dengan Media Video Terhadap Pengetahuan Remaja Tentang Seks Pranikah di SMA Al-Mas’udiyyah Bandungan Kabupaten Semarang Tahun 2019 - Putri Rahimah Mughny; Heni Setyowati; Eti Salafas (Universitas Ngudi Waluyo, 2020)
The results of the 2017 Indonesian Demographic and Health Survey (SDKI) revealed that around 2% of young women aged 15-24 and 8% of young men in the same age range had sexual relations before marriage. Teenagers in Central Java who have received reproductive health and premarital sex education are only 31.4%. So health education is provided with video on teenager knowledge about premarital sex. To analyze the effect of health education with video toward teenagers knowledge about premarital sex at Al-Mas'udiyyah Senior High School in Bandungan, Semarang district 2019. The study design used was quasi experimental pre and post test design without a control group. The population was the whole of grade X students 103 students. 24 students were taken as the sample of this research. Data were analyzed using Wilcoxon test by SPSS data version 16. Before being given the knowledge health education of teenagers in sufficient categories as many as 21 respondents (87.5%), after being given teenagers knowledge health education in the good category increased to 24 respondents (100%). There is effect between the provision of health education with video on teenager knowledge about premarital sex. There is an influence between the provision of health education with video on teenager knowledge about premarital sex at Al-Mas'udiyyah Senior High School in Bandungan, Semarang District. It is hoped that schools can provide health education with video so that they do not make students bored and can be more active in learning. ABSTRAK Hasil Survei Demografi dan Kesehatan Indonesia (SDKI) 2017 mengungkap sekitar 2% remaja wanita usia 15-24 tahun dan 8% remaja pria di rentang usia yang sama, telah melakukan hubungan seksual sebelum menikah. Remaja di Jawa Tengah mendapatkan penyuluhan kesehatan reproduksi dan seks pranikah hanya 31,4%. Sehingga diberikan pendidikan kesehatan dengan media video tentang seks pranikah. Untuk menganalisa pengaruh pendidikan kesehatan dengan media video terhadap pengetahuan remaja tentang seks pranikah di SMA Al-Mas’udiyyah Kecamatan Bandungan Kabupaten Semarang Tahun 2019. Desain yang digunakan adalah quasi experimental pre and post test design tanpa kelompok kontrol. Populasi dalam penelitian ini yaitu seluruh siswa – siswi kelas X SMA Al-Mas’udiyyah yang berjumlah 103 siswa dengan jumlah sampel 24 responden. Analisis data menggunakan uji Wilcoxon dengan pengolahan data SPSS versi 16. Sebelum diberikan pendidikan kesehatan pengetahuan remaja dalam kategori cukup sebanyak 21 responden (87,5%), setelah diberikan pendidikan kesehatan pengetahuan remaja dalam kategori baik meningkat menjadi 24 responden (100%). Ada pengaruh antara pemberian pendidikan kesehatan dengan media video terhadap pengetahuan remaja tentang seks pranikah. Ada pengaruh antara pemberian pendidikan kesehatan dengan media video terhadap pengetahuan remaja tentang seks pranikah di SMA Al- Mas’udiyyah Kecamatan Bandungan Kabupaten Semarang. Diharapkan sekolah dapat memberikan pendidikan kesehatan dengan media video sehingga tidak membuat siswa bosan dan dapat lebih aktif dalam pembelajaran